Levels of lysophosphatidic acid in cerebrospinal fluid and plasma of patients with schizophrenia. (March 2019) - Gotoh, Leo; Yamada, Misa; Hattori, Kotaro; Sasayama, Daimei; Noda, Takamasa; Yoshida, Sumiko; Kunugi, Hiroshi; Yamada, Mitsuhiko
Highlights: LPA levels in CSF and plasma were measured in patients with SZ. CSF and plasma LPA levels would not serve as a diagnostic biomarker for SZ. PANSS score negatively correlated with plasma LPA levels in male patients with SZ. Abstract: It is suggested that lysophosphatidic acid (LPA) plays a key role in the pathophysiology of schizophrenia. In this study, we measured LPA levels by enzyme-linked immunosorbent assay in cerebrospinal fluid (CSF) and plasma samples. The participants were 49 patients with schizophrenia and 49 normal healthy controls for CSF study, and 42 patients and 44 controls for plasma study. We found that LPA levels in the patients were not significantly different from those of controls in CSF (controls: 0.189 ± 0.077 µM, patients: 0.175 ± 0.067 µM; P  = 0.318) and plasma samples (controls: 0.131 ± 0.067 µM, patients: 0.120 ± 0.075 µM; P  = 0.465). On the other hand, CSF levels in medicated patients (0.162 ± 0.061 µM) were significantly lower than those observed in unmedicated patients (0.224 ± 0.067 µM, P  = 0.038), suggesting that our findings could be masked by the influence of medication with antipsychotics. Interestingly, we detected significant negative correlation between PANSS scores and plasma LPA levels, especially in males and in unmedicated patients. Our result suggests that LPA levels in CSF and plasma samples would not serve as a diagnostic biomarker, but plasma levels could be used for symptomatic assessment of schizophrenia.